(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The aim of this article is to highlight the importance of the broad freedom to choose and be chosen, or to vote and be voted for, within any representative democratic system, especially in the case of Brazil, which offers few alternatives for popular participation other than periodic voting in elections. In order to highlight the importance of popular sovereignty in state decision-making and the construction of the democratic principle around the primacy of freedom and equality, a brief evolution of democratic models in the Western world is presented, starting with the ideal model of direct democracy in ancient Greece and ending with the consolidation of the representative model in the modern state. With these assumptions in place, the aim is to demonstrate that legislation restricting political rights in Brazil, especially the right to vote, contributes to the democratic deficit and the crisis of representativeness that the country is experiencing. To this end, an analytical study of Brazil’s ineligibility law is presented, with its historical and political origins, drawing a comparison with the human rights treaties to which the country is a signatory and precedents judged by the Inter-American Court of Human Rights, with erga omnes effects, which are not being respected in the country.